Assessment of Functioning in Older Adults Hospitalized in Long-Term Care in Portugal: Analysis of a Big Data - Ramos, Ana; Fonseca, César; Pinho, Lara; Lopes, Manuel; Brites, Rui; Henriques, Adriana (Frontiers in Medicine, 2022)
Background: Functioning assessment is a key tool for health professionals to characterize the person's degree of dependence and plan care. The objectives were: 1) to assess the variables that characterize the concepts of functioning of older adults hospitalized in the national network of integrated continuous health care in Portugal; and 2) compare the conceptual frameworks used in this net-work with the International Classification of Functioning, Disability and Health (ICF). Methods: Longitudinal, retrospective study with 171 414 individuals aged 65 years and over. Principal Components Analysis was realized to reduce the number of variables, previous suggested by a scoping review, about the concepts that characterize the functionality. Then, was made a consensus meeting, where the items were matched with the ICF. Results: The average age of the sample is 80.17 years old (SD = 7.383), predominantly fe-male (59%), without a spouse (54%) and with less than 6 years of education (56.4%). Four concepts were grouped: mobility, life daily activities, instrumental activities and cognitive status that demonstrated good internal consistency. Most items correspond to ICF, except for the item “taking medication”. Conclusion: Theoretical and conceptual similarities support the use of instru-ments based on the ICF in Portugal's health care network. We suggest that ICF also encompasses a specific dimension related to medication management, given its importance for people's health.